An Empirical Study on the Performance of the “Head-and-Shoulders” Technical Strategy - Lan, Xin (2014)
Abstract: The performance of technical analysis has long been a controversial topic between the practitioners and academics. In order to examine the performance of one of the most popular technical trading rules, the head-and-shoulders strategy, the study uses hourly historical data over the period of 01/06/2004-01/06/2014 on six currency pairs in foreign exchange market. Returns and profits were compared with buy-and-hold strategy and the results suggested that the head-and-shoulders strategy unperformed the buy-and-hold strategy.